New developments in sustainable waste-to-energy systems. (November 2021) - Loizidou, Maria; Moustakas, Konstantinos; Rehan, Mohammad; Nizami, Abdul-Sattar; Tabatabaei, Meisam
Abstract: This virtual special issue published in Renewable and Sustainable Energy Reviews contains 25 high-quality selected extended papers presented at the HERAKLION 2019 7th International Conference on Sustainable Solid Waste Management held in Heraklion, Crete in Greece from 26th to June 29, 2019. The articles published in this special issue focus on recent developments in sustainable waste-to-energy systems and waste management practices and highlight the critical challenges and potential solutions. The editorial paper aims to give a brief overview of the key findings and future perspectives proposed in these 25 selected papers. It is worth noting that although the articles presented in this special issue covered a wider range of topics, they are categorized into five categories. These include the latest developments in 1) waste-to-energy technologies, 2) biofuels and bioenergy, 3) waste valorization, 4) emerging renewable and sustainable energy systems, and finally, 5) biorefineries and circular economy. Highlights: Twenty five high quality peer-reviewed papers were selected from HERAKLION 2019 Conference. The mian theme of sustainable waste-to-energy systems catogorised into five topics. It will support advancement of waste-to-energy technologies and circular economy.